α-Synuclein: A Multifunctional Player in Exocytosis, Endocytosis, and Vesicle Recycling - Huang, Mingzhu; Wang, Bianbian; Li, Xiaopeng; Fu, Chongluo; Wang, Changhe; Kang, Xinjiang (Frontiers in Neuroscience, 2019)
α-synuclein is a presynaptic enriched protein involved in the pathogenesis of Parkinson’s disease, however the physiological roles of α-synuclein remain poorly understood. Recent studies have indicated a critical role of α-synuclein in the sensing and generation of membrane curvature during vesicular exocytosis and endocytosis. It has been known to modulate the assembly of SNARE complex during exocytosis including vesicles docking, priming and fusion steps. Growing evidence suggests that α-synuclein also plays critical roles in the endocytosis of synaptic vesicles. It also modulates the availability of releasable vesicles by promoting synaptic vesicles clustering. Here, we provide an overview of recent progresses in understanding the function of α-synuclein in the regulation of exocytosis, endocytosis and vesicle recycling under physiological and pathological conditions.